Lectotypification and a new name in Palicourea for the Brazilian Psychotria dusenii Standl. (Rubiaceae), with remarks on morphology and taxonomy - Torres-Leite, Filipe; Carmo, João Afonso Martins Do; Bruniera, Carla Poleselli; Carrijo, Tatiana Tavares; Goldenberg, Renato (Phytotaxa, 2024)
Here we propose a lectotypification and a new name for the Brazilian Psychotria dusenii Standl. to be treated under Palicourea Aubl. The name Psychotria dusenii sensu Standley is illegitimate because it was previously assigned to an African Psychotria L. species described by K. Schumann. The new name proposed is Palicourea roseocalycina Torres-Leite.